PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN TOJO UNA-UANA - Suleman, Gusnar A. (Katalogis, 2017)
The study intends to determine and analyze simultaneous influence of work discipline and environment on the performance of Officials at The Secretariate of Regional Parliament of Tojo Una-Una District; to determine and analyze partial influence of work discipline on the performance of Officials at The Secretariate of Regional Parliament of Tojo Una-Una District; toÂ determine and analyze partial influence of environment on the performance of Officials at The Secretariate of Regional Parliament of Tojo Una-Una District. Population consists of 35 officials at The Secretariate of Regional Parliament of Tojo Una-Una District who selected through census method. The study finds that both independent variables have simultaneous influence on officialsâ€™ performance with Rsquare value of 0.679; partially, work discipline has significant influence with coefficient regression of 0.693 while the variable of work environment has coefficient regression of 0.189.